Termites (Insecta: Isoptera) from Punjab with New Distributional Records - Kumar, Sachin; Thakur, R. K. (Indian Forester, 2013)
Twenty-seven species of termites belonging to two families (Rhinotermitidae and Termitidae) under eleven genera (Heterotermes,Coptotermes, Speculitermes, Amitermes, Synhamitermes, Eremotermes, Microcerotermes, Dicuspiditermes, Odontotermes, Microtermes and Trinervitermes) are reported from Punjab. Out of 27 species, fifteen termite species are reported first time from Punjab.